STUDENTS’ MOTIVATION ON DEEP LEARNING APPROACH IN LEARNING ENGLISH THROUGH TECHNOLOGY ENHANCED LANGUAGE LEARNING (TELL) - Ida Maulida; Ninuk Lustyantie; Uwes Anis Chaeruman (Media Bina Ilmiah, 2024)
The role of technology in language learning has evolved significantly over the past few decades, with the advent of various tools and applications that enhance the educational experience. Technology Enhanced Language Learning (TELL) has emerged as a pivotal approach, integrating digital resources to facilitate language acquisition and improve student engagement. This introduction explores the multifaceted impact of technology on language learning, highlighting its benefits, challenges, and implications for both learners and educators. This research aims to analyze students' motivation in learning English by applying deep learning strategies through the Technology Enhanced Language Learning (TELL). This research uses a mixed approach, where quantitative data is obtained through motivation questionnaires, and qualitative data is obtained through in-depth interviews with participating students. The sample was taken by purposive sampling with a total of 34 students for the quantitative survey and for in-depth interviews. There are several findings in improving language learning with TELL: 1) students are more independent in learning language with TELL but need teacher assistance in further understanding the material 2) The teaching materials available in application learning lead to general English learning, while students also have to learn academic English 3) Students feel that studying with applications is more relaxing than studying with friends for several influencing factors. Students’ motivation to increase learning English with the Deep Learning approach with TELL provides insight into how technology and deep learning approaches can increase students' motivation in learning English, as well as providing recommendations for educators to integrate technology more effectively in the learning process.